Honest Grading, Grade Inflation and Reputation - Tim Ehlers; Robert Schwager (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
When grades lose their informative value because the percentage of students receiving the best grade rises without any corresponding increase in ability, this is called grade inflation. Conventional wisdom says that such grade inflation is unavoidable since it is essentially costless to award good grades. In this paper, we point out an effect driving into the opposite direction: Grade inflation is not actually costless, since it has an impact on future cohorts of graduates, or, put differently, by grading honestly, a school can build up reputation. Introducing a concern for reputation into an established signaling model of grading, we show that this mechanism reduces or even avoids grade inflation.
Keywords: I21; I23; D82; 330